MR-Guided Radiotherapy for Rectal Cancer: Current Perspective on Organ Preservation - Boldrini, Luca; Intven, Martijn; Bassetti, Michael; Valentini, Vincenzo; Gani, Cihan (Frontiers in Oncology, 2021)
Online MRI-guided radiotherapy (MRgRT) is one of the most recent technological advances in radiotherapy. MRgRT permits the visualization of tumorous and healthy tissue while the patient is on the treatment table and online daily plan adaptations following the observed anatomical changes. In the context of rectal cancer, online MRgRT is a very promising modality due to the pronounced geographical variability of tumor tissues and the surrounding healthy tissues. This current paper will discuss the possible applications of online MRgRT, in particular, in terms of radiotherapy dose escalation and response prediction in organ preservation approaches for rectal cancer.